Association between the duration of mothers’ digital media use while with their children and two-year-old children’s development from the Japan Environment and Children’s Study - Yuka Ogata; Takatomo Matsumoto; Yuichi Suzuki; Toshie Nishigori; Aya Goto; Akiko Sato; Toma Fukuda; Karin Imaizumi; Hyo Kyozuka; Tsuyoshi Murata; Yuichi Nagasaka; Hidekazu Nishigori; et al. (Scientific Reports)
Abstract Few studies have evaluated the association between the duration of mothers’ digital media use (including mobile phones, tablets, and PCs) while with their children and children’s development. Using data from the Japan Environment and Children’s Study, we explored this relationship through multiple regression analysis. Self-administered questionnaires measured the duration of mothers’ digital media use. Developmental outcomes were assessed using the Kyoto Scale of Psychological Development 2001 (KSPD), administered to two-year-olds by trained examiners. The KSPD assessed three domains: postural-motor (fine and gross motor abilities), cognitive-adaptive (non-verbal cognitive capacity and visual-spatial comprehension), and language-social (interpersonal relationships, socialization, and verbal abilities). The analysis included 3,786 mother–child pairs with complete exposure data, outcomes, and covariates. The children of mothers who used digital media for one hour or more exhibited lower language-social development quotients compared with those whose mothers did not use digital media while with them. Furthermore, the children of mothers who used digital media for two hours or more showed a lower total developmental quotient compared with those whose mothers did not use digital media. The use of digital media by mothers for more than one hour per day while with their children is thus negatively associated with language development in two-year-olds, while use for more than two hours is negatively associated with children’s development.